Effect of management systems in soil physical attributes - Spera, Silvio Tulio (2007)
Inadequated soil tillage can induce the formation of compacted layer near soil surface. Soil physical attributes were assessed after sixteen years of distinct soil management on a typical dystrophic red latosol located in Passo Fundo, Rio Grande do Sul State, Brazil. Four soil tillage systems – no-tillage, minimum tillage, conventional tillage using a disk plow plus disk harrow, and conventional tillage using a moldboard plow plus disk harrow – and three crop rotation systems - system I (wheat/soybean), system II (wheat/soybean and common vetch/corn), and system III (wheat/soybean, white oat/soybean, and common vetch/corn) were evaluated. A randomized complete block design, with split-plots and three replicates, was used. The main plots were soil tillage systems, while the split consisted of crop rotation systems. Soil cores were also collected in a fragment of subtropical forest adjacent to the experiment. No-tillage showed higher soil density than conventional tillage using a moldboard plow plus disk harrow, minimum tillage, and subtropical forest. The subtropical forest showed the highest total porosity and macroporosity, as compared to the all soil tillage systems and crop rotation systems, and the lowest bulk density and microporosity. Soil bulk density was increased from the top layer (0-5 cm) to deeper layer (10-15 cm) in all soil tillage systems and rotation systems and presented the lowest total porosity and macroporosity.